Predicting institutionalization after Subacute Stroke Rehabilitation using the 12-Item World Health Organization Disability Assessment Schedule - Sinikka Tarvonen-Schröder; Mari Koivisto (Medical Journals Sweden, 2023)
Objective: To evaluate the utility of the 12-item World Health Organization Disability Assessment Schedule (WHODAS-12) in predicting institutionalization after subacute stroke rehabilitation. Design: Prospective observational study. Methods: On a specialized rehabilitation ward, discharge WHODAS-12 scores of 156 consecutive patients (24-h National Institutes of Health Stroke Scale (NIHSS) ≥ 15) and assessment from their proxies were compared, and receiver operating characteristic curves for predicting institutionalization were generated. Clinician-rated assessments of functioning were applied for comparison. Results: Thirty-three percent of the patients were unfit to respond, due to the consequences of major stroke. However, both patient and proxy WHODAS-12 sum scores differentiated the community (n = 70) and institution (n = 86) groups (p = 0.02 and p < 0.0001, respectively), the discriminative accuracy (area under the curve; AUC) being 0.63 and 0.79, respectively. In proxy assessments, the institutionalized patients were significantly more impaired in all item comparisons except for emotions and concentrating. Ability to participate differentiated the groups as accurately as activities (AUC 0.75 vs 0.78, respectively). The corresponding discriminative accuracy of the clinician-rated World Health Organization (WHO) minimal generic dataset sum score and modified Rankin Scale were 0.74 and 0.79 (p < 0.0001), respectively. Conclusion: Despite its brevity and subjectivity, the WHODAS-12 from proxies has shown high accuracy in predicting institutionalization after subacute rehabilitation of individuals with major stroke, the impact of participation being as relevant as that of activities. LAY ABSTRACT This study investigated the utility of the patient- and proxy-rated 12-item World Health Organization Disability Assessment Schedule (WHODAS-12) in predicting institutionalization after rehabilitation of patients with major stroke. At discharge from rehabilitation, a median of 3 months after stroke onset, 33% of the 156 patients were not fit to respond due to the consequences of major stroke. Both of these brief measures differentiated those discharged to community from those institutionalized. WHODAS from proxies was more accurate in predicting institutionalization, and as accurate as the clinician-rated gold-standard measure, the modified Rankin Scale. Both components of WHODAS, i.e. activities and participation, were equally relevant in differentiating the 2 discharge groups. WHODAS-12 is recommended as part of individualized patient- and family-centered discharge planning after rehabilitation of patients with major stroke.